Pengaruh Organizational Citizenship Behaviour (OCB), Kepuasan Kerja dan Komitmen Organisasi terhadap Turnover Intention Karyawan pada Hotel Mitra Park View Kota Semarang - Harahap, Divia Salsabila Maghfirotin (Faculty of Economics and Business Universitas Dian Nuswantoro, 2022)
This research is to find out the impact of Organizational Citizenship Behavior (OCB), Job Satisfaction, Organizational Commitment to Turnover Intention on employees of Hotel Mitra Park View Semarang City. The independent variables in this research consist of Organizational Citizenship Behavior (OCB), Job Satisfaction, Organizational Commitment, and the dependent variable, namely Turnover Intention. Questionnaires were distributed to 65 employees using the quota sampling method. The data obtained were analyzed using IBM SPSS Statistics 24 software. The results of this research show that only the Organizational Commitment variable has a significant effect on the Turnover Intention variable and the other two variables have no effect on the Turnover Intention of the employees of Hotel Mitra Park View Semarang City. Riset ini untuk mengetahui dampak Organizational Citizenship Behavior (OCB), Kepuasan Kerja, Komitmen Organisasional terhadap Turnover Intention pada karyawan Hotel Mitra Park View Kota Semarang. Variabel bebas dalam riset ini terdiri dari Organizational Citizenship Behavior (OCB), Kepuasan Kerja, Komitmen Organisasional, dan serta variabel terikat yaitu Turnover Intention. Penyebaran kuesioner dilakukan kepada 65 karyawan dengan menggunakan metode quota sampling. Data yang diperoleh dianalisis dengan menggunakan software IBM SPSS Statistics 24. Hasil riset ini menunjukan bahwa hanya variable Komitmen Organisasi berpengaruh signifikan terhadap variabel Turnover Intention dan dua variable lainnya tidak berpengaruh terhadap Turnover Intention pada karyawan Hotel Mitra Park View Kota Semarang. Keywords:organizational citizenship behaviorjob satisfactionorganizational commitmentturnover intention